A novel exploration for traveling wave solutions to the integrable equation of wave packet envelope - Kaplan, Melike; Akbulut, Arzu (Elsevier BV, 2022)
In this paper, with the aid of symbolic computation, different types of traveling wave solutions to a model involving an integrable equation for wave packet envelope have been presented. The exp(−Φ(ξ))-expansion and modified Kudryashov procedures have been adopted and finally 3D and 2D graphics of the obtained solutions have been plotted. The obtained results are including dark, breather, bright, and periodic soliton solutions.
Keywords: T57-57.97; Applied mathematics. Quantitative methods; Symbolic computation; Partial differential equation; Exact solutions